Performance analysis of OFDM-MIMO for transmitting medical image - Bintu, Shah Tabassum; Akter, Shila; Nahar, Sabikun (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.